2020
DOI: 10.1021/acs.jpcc.9b11651
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Crystal Morphology of Potassium Chloride Controlled by Optical Trapping

Abstract: Dynamic morphology evolution of potassium chloride (KCl) crystals was demonstrated by surface optical trapping with a focused continuous-wave near-infrared laser. Optical trapping at an air/solution interface triggered the crystallization, and then, the dynamic change in crystal morphology was observed in real time. We observed three different crystal morphologies of needle, rectangle, and cubic at the early stage of crystallization. As the laser power increases, the probability of generation of a cubic crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…This optical scattering and propagation at interface holds also for molecular solution, which explains the molecular crystallization of amino acids , 23,39 and inorganic compounds such KCl 40 . We have demonstrated that the optically generated crystals are much larger than the focused laser beam size (about 1 µm 2 ) and they can even enlarge up to a few tens of µm 2 .…”
Section: Introductionmentioning
confidence: 86%
“…This optical scattering and propagation at interface holds also for molecular solution, which explains the molecular crystallization of amino acids , 23,39 and inorganic compounds such KCl 40 . We have demonstrated that the optically generated crystals are much larger than the focused laser beam size (about 1 µm 2 ) and they can even enlarge up to a few tens of µm 2 .…”
Section: Introductionmentioning
confidence: 86%
“…1a). While OTIC has been performed using a NIR laser in the past, [23][24][25][26][27][28] we employed a 532 nm laser that served the dual role of inducing a crystal nucleation and Raman excitation (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Optical trapping induced crystallization (OTIC) was first demonstrated by Sugiyama et al in 2007 by focusing a near infrared (NIR) laser in supersaturated glycine/D2O solution. 23 Since the discovery, OTIC has been applied to a variety of systems, [24][25][26] and furthermore high quality single crystals can be prepared while the polymorphs can be controlled by laser polarization. 26,27 Our approach applies OTIC to spatially control a single crystal nucleation event (i.e.…”
mentioning
confidence: 99%
“…1a). While OTIC has been performed using a NIR laser in the past, [23][24][25][26][27][28] we employed a 532 nm CW laser that served the dual role of inducing a crystal nucleation and Raman excitation (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Optical gradient force is, however, not large enough to trap a single molecule, and therefore it is generally assumed that the crystallization occurs as a result of local concentration increase by trapping aggregates in solution. Since the discovery, OTIC has been applied to a variety of systems, [24][25][26] and furthermore high quality single crystals can be prepared while the polymorphs can be chosen by laser polarization. 26,27 Our approach applies OTIC to spatially control a single crystal nucleation event (i.e.…”
mentioning
confidence: 99%